Harrison Birtwistle Responses: Sweet disorder and the carefully careless for piano and orchestra, Royal Festival Hall, London. (17th April 2015) - Broad, Leah
<x content-type="archive" xml:space="preserve">Abstract</x> 2014, Sir Harrison Birtwistle's 80th birthday year, witnessed a plethora of events celebrating his music, from the Barbican's 'Birtwistle at 80' series to the 'In Broken Images' concerts at the Southbank Centre. Included in the latter was the UK premiere of his new concerto for piano and orchestra, Responses: Sweet disorder and the carefully careless, performed on 6 December 2014 by Pierre-Laurent Aimard and the London Philharmonic Orchestra under the direction of Vladimir Jurowski. Birtwistle describes the concerto as addressing the problem of 'the relationship between the piano and the orchestra', with the subtitle (taken from essays by architect Robert Maxwell) expressing the 'essence' of his composition.